Dinamika usaha penangkapan ikan Pulau Sapeken 1904-1914 - Nugroho, Fajar (Universitas Negeri Malang, 2023)
Fisheries is one of the two non-agricultural sectors that played an important role in the economy of the people of Sapeken Island in the late 19th to early 20th centuries. This study aims to explain that the role of the fishing elite (owners of capital and moneylenders) succeeded in bringing the fishing business sector to fish in the direction of growth. But on the other hand, the existence of this group makes fishermen bound to the monopoly system they control. The method used in this study is the historical method, namely topic selection, heuristics, criticism, interpretation, and historiography. The findings produced in this study are that the fisheries sector is a place of business for the elite group of fishermen, they control and dominate this sector starting from the provision of capital, equipment, production, and distribution of fish trade. This condition ultimately results in fishermen not being able to develop their own business network, so that the productivity of the fishing effort becomes erratic. Perikanan merupakan salahsatu dari dua sektor di luar pertanian yang memiliki peranan penting dalam perekonomian masyarakat Pulau Sapeken pada akhir abad 19 sampai awal abad ke 20, munculnya kelompok elit nelayan (pemilik modal dan pelepas uang) berhasil membawa sektor usaha penangkapan ikan ke arah pertumbuhan. Namun di sisi lain, dengan adanya kelompok tersebut membuat para nelayan menjadi terikat terhadap sistem monopoli yang dikendalikannya. Sektor perikanan menjadi tempat ladang bisnis bagi kelompok elit neleyan, mereka menguasi dan mendominiasi sektor ini mulai dari penyediaan modal, peralatan, produksi, dan distribusi perdagangan ikan. Kondisi ini pada akhirnya mengakibatkan para nelayan tidak dapat mengembangkan jaringan usahanya sendiri, sehingga produktivitas usaha penangkapan ikan menjadi tidak menentu.